The Louisville and Nashville Railroad, 1850-1963 - Herr, Kincaid A. (Book collections on Project MUSE., 2009)
When the Louisville and Nashville Railroad was founded in 1850, it was the first major railroad in the west, and the only one headquartered in Kentucky. In the twentieth century, the L & N grew into one of the nation's major rail systems, reaching from the Great Lakes to the Ohio River Valley and down to Florida and the Gulf Coast. Kincaid Herr worked for the Louisville and Nashville for more than forty years, and this book originated as a series of articles that he wrote for L & N Magazine between 1939 and 1942. After various printings through the 1940s and '50s, this fifth edition, completely re.